Learning in the global era : international perspectives on globalization and education - Suárez-Orozco, Marcelo M., 1956- (University of California Press ; Ross Institute, 2007)
An international school of leading scholars, policy makers and educators take on some of the most difficult and controversial issues of our time in this exploration of how globalization is affecting education around the world.